Determination of the maximum inhibitory dilution of cetylpyridinium chloride-based mouthwashes against Staphylococcus aureus: an in vitro study - Watanabe, Evandro (2008)
The aim of this in vitro study was to determine the maximum inhibitory dilution (MID) of four cetylpyridinium chloride (CPC)based mouthwashes: CPC+Propolis, CPC+Malva, CPC+Eucaliptol+Jua+Roma+Propolis (Natural Honey (R)) and CPC (Cepacol (R)), against 28 Staphylococcus aureus field strains, using the agar dilution method. Decimal dilutions ranging from 1/10 to 1/655,360 were prepared and added to Mueller Hinton Agar. Strains were inoculated using Steers multipoint inoculator. The inocula were seeded onto the surface of the culture medium in Petri dishes containing different dilutions of the mouthwashes. The dishes were incubated at 37 degrees C for 24 h. For readings, the MID was considered as the maximum dilution of mouthwash still capable of inhibiting microbial growth. The obtained data showed that CPC+Propolis had antimicrobial activity against 27 strains at 1/320 dilution and against all 28 strains at 1/160 dilution, CPC+Malva inhibited the growth of all 28 strains at 1/320 dilution, CPC+Eucaliptol+Jua+Roma+Propolis inhibited the growth of 2 strains at 1/640 dilution and all 28 strains at 1/320 dilution, and Cepacol (R) showed antimicrobial activity against 3 strains at 1/320 dilution and against all 28 strains at 1/160 dilution. Data were submitted to Kruskal-Wallis test, showing that the MID of Cepacol (R) was lower than that determined for the other products (p<0.05). In conclusion, CPC-mouthwashes showed antimicrobial activity against S. aureus and the addition of other substances to CPC improved its antimicrobial effect.